BICAO-induced ischaemia caused depressive-like behaviours and caspase-8/-9-dependent brain regional neural cell apoptosis in mice. Issue 1 (17th December 2017) - Liu, Shuiqiao; Han, Song; Dai, Qingqing; Li, Shujuan; Li, Junfa
Abstract : Introduction: Cerebral ischaemia-induced depression is among the most frequent neuropsychiatric consequences and adversely impact the prognosis and recovery of patients. Although several brain regions have been implied in the development of ischaemia-induced depression, the brain region-specific neural cell apoptosis pathways have not been clarified yet. Methods: In this study, bilateral internal carotid artery occlusion (BICAO) mouse model was established to induce cerebral ischaemia. Sucrose preference, tail suspension and forced swim tests were conducted on mice at 7, 21 and 30 days after BICAO treatment. In addition, brain regional ischaemic neuron loss was investigated by using immunofluorescent staining of neuronal nuclei (NeuN) and caspase-8/-9-dependent cell apoptosis was also examined by western blot analysis. Results: BICAO-induced cerebral ischaemia resulted in decreased sucrose preference and increased immobility times, which were representative depressive-like behaviours of mice until 30 days after BICAO treatment compared with Sham-operated mice. This outcome was associated with significant neuron loss by using immunofluorescent staining and increased cleavage levels of pro-caspase-3/-8/-9, but not pro-caspase-12, by western blot analysis in hypothalamus, midbrain, prefrontal cortex and hippocampus of mice. Conclusions: This study showed that BICAO-induced ischaemia caused depressive-like behaviours and caspase-8/-9-dependent neural cell apoptosis in several brain regions, including hypothalamus and midbrain of mice.